'German Theory': Cosmopolitan geographies, counterfactual histories and the (non)travel of a 'German Foucault'. (October 2021) - Korf, Benedikt
In this paper, I propose the notion of 'German Theory' to allude to the processes of translation and circulation of theoretical ideas discussed in the German humanities and German geography across and beyond the linguistic boundaries of its origin. However, these ideas did not travel, at least not to Anglophone geography. This paper investigates why not, and it maps out the lost theoretical potential that has been foregone as a result. 'German Theory' is thus read here as a potentiality that has not actualised. More specifically, this paper studies the reception of Foucault, as it emerged in two distinct territories of thought, each with their own interpretation: first, Kittler's work on the materiality of discourse in German humanities, and second, the 'discourse school' in German geography. The latter's insistence on the textuality of discourse disconnected their Foucault reception not only from Kittler's, but equally so from ongoing debates in Anglophone geography. By reflecting on why the 'German Foucault' did not travel to Anglophone geography, I raise a speculative epistemological question about the im/potentiality of 'German Theory': could a more cosmopolitan theory have emerged from a circulation of these ideas had they travelled across linguistic boundaries?